Pengaruh suhu dan waktu infusa terhadap kandungan total flavonoid dan total fenolik pada infusa daun benalu (Scurrula feruginea) (Jack) Danser - Puji Puji; Fatridha Yansen; Azuxetullatif Azuxetullatif; Boy Andre (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Scurrula ferruginea (Jack) Danser has long been utilized in Indonesian traditional herbal medicine owing to its diverse bioactive constituents; however, the influence of preparation conditions on its phytochemical profile remains insufficiently characterized. This study investigated the effects of infusion temperature (60°C, 70°C, and 80°C) and steeping duration (15, 20, and 30 minutes) on the total flavonoid content (TFC) and total phenolic content (TPC) of S. ferruginea leaf infusions, employing a 3×3 Completely Randomized Factorial Design with two replicates. Spectrophotometry UV-Vis was performed to quantify TFC and TPC. Two-Way ANOVA depicted that infusion temperature exerted a highly significant effect on TFC (p< 0.001), whereas infusion duration did not significantly influence either variable. A statistically significant temperature and duration interaction was detected for TFC (p<0.001), indicating that the temperature-dependent flavonoid extraction is contingent upon the duration applied. Post hoc Tukey HSD analysis demonstrated that infusion at 70°C yielded significantly lower TFC (1.371 mg QE/g) relative to both 60°C (1.741 mg QE/g) and 80°C (1.687 mg QE/g), with no significant difference observed between the latter two temperatures. TPC remained comparatively stable across all treatment combinations, with temperature, duration, and their interaction all failing to exert a statistically significant effect. These findings establish infusion temperature as the dominant determinant of flavonoid extractability from S. ferruginea leaves, and indicate that a minimum steeping duration of 15 minutes at 60°C or 80°C is sufficient to maximize TFC without compromising TPC. This study provides an evidence-based foundation for optimizing the aqueous preparation of S. ferruginea leaf infusion as a candidate functional herbal beverage.